(untitled) (Relevant Tomorrow / Aktualu rytoj, 2025)
The case of Eugene de Kock epitomizes the way in which South Africa tried to come to terms with its Apartheid past after 1994. His conviction, his imprisonment, his admission of guilt, and his eventual release gave rise to a broad national debate in South Africa and also to the question of how and under what conditions national reconciliation is possible. At the same time, it is also an example of how a state can shape collective memory. De Kock’s example shows that criminal justice, as well as amnesty and rehabilitation, can promote a form of remembrance that emphasizes the role of the individual more than social and political issues and challenges. The article aims to contribute to a better understanding of the delicate balance between justice and reconciliation, as well as between justice and memory.